Advancements in research to mitigate residual risk of atherosclerotic cardiovascular disease - Fan Shi; Jinjin Dou; Xiwu Zhang (European Journal of Medical Research)
Abstract Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death worldwide. Although low-density lipoprotein cholesterol (LDL-C) levels are well controlled by current therapies, the residual risk of ASCVD remains, and adverse cardiovascular events remain a major clinical problem worldwide. Therefore, it is necessary to identify the sources of remaining risks and formulate targeted strategies to solve these problems. In recent years, the role of gut microbiota has been rediscovered, including trimethylamine N-oxides (TMAO), secondary bile acids, lipopolysaccharides (LPS), and short chain fatty acids (SCFAs), which have been found to play a key role in the pathogenesis of ASCVD. New lipid-lowering therapeutic targets are currently under development, such as triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and lipoprotein(a). Other studies of novel therapeutic agents that target inflammatory pathways, the immune system, etc., are also seeking to address the residual risks associated with ASCVD. The purpose of this review is to evaluate residual risk factors and novel therapeutic strategies for ASCVD, with a focus on the most recent therapeutic advancements, mechanisms, and clinical treatments.